Monitoring of Single Wire Earth Return Systems using Power Line Communication - Gay, D.; Thompson, A.; Than Oo, A.; Wolfs, Peter (The University of Adelaide, 2009)
As demand for power increases in rural areas serviced by Single Wire Earth Return (SWER) networks, distribution issues are becoming increasingly evident. Voltage regulation and system capacity concerns are driving utilities toward using smarter compensation devices for network control in an attempt to provide longevity for aging SWER infrastructure. To date, despite increasing complexity in power delivery over SWER, no effective network monitoring solutions have been proposed. This paper examines the case for network monitoring and centralised management of smart compensation devices via Power Line Communications (PLC). After establishing advantages in network monitoring, regulation and maintenance for SWER networks, narrowband and broadband PLC issues are reviewed. The channel capacity of typical SWER conductors is then evaluated and compared to data throughput requirements derived from existing infrastructure to validate the applicability of developing PLC over SWER infrastructure.